The traditional cellars: heritage forgotten in the culture of the wine in the designation of origin Cigales (Castilla y León, Spain) - Fernández Portela, Julio; García Velasco, Miguel Ángel (Geographicalia, 2014)
Traditional cellars are part of the artistic and ethnographic heritage existing in some parts of Castilla y León. For municipalities that make up the Designation of Origin Cigales, these facilities have gained an important weight because of its abundance with more than 1,200 cellars scattered throughout the territory. Currently, these cellars have suffered a series of major changes which are modifying the traditional landscape in which they are located. If you walk through the typical cellar neighbourhoods in these municipalities you can see all the interventions made by man, which in most cases have not followed a common pattern consistent with the landscape. Aspects that have contributed more to the loss of identity of these spaces, making it necessary to raise a number of proposals to keep these so characteristic neighbourhoods.